Preparing European Nephrology for the next pandemic: lessons from the ERACODA collaboration. Issue 3 (16th November 2022) - Vart, Priya; Duivenvoorden, Raphaël; Franssen, Casper F M; Hemmelder, Marc H; Jager, Kitty J; Hilbrands, Luuk B; Noordzij, Marlies; Abramowicz, Daniel; Basile, Carlo; Covic, Adrian; Crespo, Marta; Massy, Ziad A; et al.
ABSTRACT: Owing to the vulnerability of patients with chronic kidney disease to infectious diseases, the coronavirus disease 2019 (COVID-19) pandemic has been particularly devastating for the nephrology community. Unfortunately, the possibility of future COVID-19 waves or outbreaks of other infectious diseases with pandemic potential cannot be ruled out. The nephrology community made tremendous efforts to contain the consequences of the COVID-19 pandemic. Despite this, the COVID-19 pandemic has highlighted several shortcomings in our response to the pandemic and has taught us important lessons that can be utilized to improve our preparedness for any future health crises of a similar nature. In this article we draw lessons from the European Renal Association COVID-19 Database (ERACODA) project, a pan-European collaboration initiated in March 2020 to understand the prognosis of COVID-19 in patients on kidney function replacement therapy. We discuss the challenges faced in generating timely and robust evidence for informed management of patients with kidney disease and give recommendations for our preparedness for the next pandemic in Europe. Limited collaboration, the absence of common data architecture and the sub-optimal quality of available data posed challenges in our response to COVID-19. Aligning different research initiatives, strengthening electronic health records, and involving experts in study design and data analysis will be important in our response to the next pandemic. The European Renal Association may take a leading role in aligning research initiatives via its engagement with other scientific societies, national registries, administrators and researchers.